Brain spectroscopic measures of glutamatergic and neuronal metabolism and glial activation influence white matter integrity in bipolar depression. (October 2022) - Bravi, Beatrice; Bollettini, Irene; Di Pasquasio, Camilla; Falini, Andrea; Colombo, Cristina; Zanardi, Raffaella; Poletti, Sara; Benedetti, Francesco
Highlights: Bipolar patients show higher levels of Glx/NAA, Glx, and mI compared to controls. Higher Glx/NAA ratio is associated with lower fractional anisotropy. Higher mI is associated with lower fractional anisotropy. We observed a joint negative association of Glx/NAA and mI on fractional anisotropy. Abstract: Bipolar disorder (BD) is associated with alterations in white matter (WM) microstructure, glutamatergic neurotransmission, and glia activity. Previous studies showed higher concentrations of glutamate (Glu), glutamate+glutamine (Glx), and reduced N-acetyl-aspartate (NAA) in BD. We investigated brain concentrations of Glu, Glx, NAA, mI as indirect marker of microglia activation, and Glx/NAA ratio as index of neuronal damage through 1 H-MR, and WM integrity with Tract-Based Spatial Statistics in 93 depressed BD patients and 58 healthy controls (HC). We tested for linear effects of cited spectroscopic metabolites on DTI measures of WM integrity with general linear models for each group, then performing a conjunction analysis of Glx/NAA and mI concentration on the same measures. Statistical analyses (whole sample) revealed higher concentration of Glx/NAA, Glx and mI in BD patients compared to HC, and a positive association between mI and the ratio. DTI analyses (87 BD and 35 HC) showed a significant association of Glx/NAA ratio, and mI with WM microstructure. Conjunction analysis revealed a joint negative association between Glx/NAA and mI with fractional anisotropy. This is the first study showing an association between brain metabolites involved in neuronal damage, and glial activation and the alterations in WM consistently reported in BD.